Kebiasaan Makanan Belangkas, Tachypleus gigas (Müller 1785) dan Carcinoscorpius rotundicauda (Latreille 1802) di Perairan Pesisir Balikpapan, Kalimantan Timur - Rani Nuraisah; Naila K Aini; Ali Mashar; Zairion Zairion; Yuni P Hastuti; Peter Funch; Yusli Wardiatno (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2020)
Horseshoe crabs are living fossils found in Indonesia. This study examined the food habit of horseshoe crabs (Carcinoscorpius rotundicauda and Tachypleus gigas) collected from Balikpapan coastal waters, East Kalimantan. Horseshoe crabs were captured using gill nets and picked by hand along the Balikpapan coast. The width of the prosoma and the body weight of each individual were measured, and the gut contents were analysed to determine the preponderance index, food niche breadth, and niche overlap. Carcinoscorpius rotundicauda prosoma widths ranged from 4.1 to 15.4 cm and those of Tachypleus gigas ranged from 2.8 to 24 cm. Eight food items were found in the gut of the horseshoe crabs, namely: bivalves, gastropods, scaphopoda, polychaetes, echinoderms, crustaceans, leaf litter and others. Based on the preponderance index, gastropods were the main food item of the two horseshoe crab species. In accordance to the food composition the horseshoe crabs inhabiting Balikpapan coastal waters are categorized as benthivores.